2015
DOI: 10.3329/sjm.v4i1.22755
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of antibiotic resistant pathogenic bacteria in vegetable items sold by local and super shops in Dhaka city

Abstract: The present study was carried out to investigate the microbiological quality and antibiotic resistance patterns of pathogenic bacteria isolated from vegetable samples. A total of 14 vegetable samples, 7 from local and 7 from super shops, were randomly collected from different locations of Dhaka city. Concentrations of total heterotrophic bacteria, total coliform, faecal coliform, Pseudomonas spp., Listeria spp. and Staphylococcus aureus were enumerated from each sample by serial dilution and spread plate techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Again, foodborne illness due to contaminated vegetables increased many folds worldwide and many research studies reported that the presence of pathogenic bacteria like E. coli O157:H7, Salmonella spp., Listeria spp., Staphylococcus spp., Yersinia enterocolitica etc. in various fresh vegetable samples of Dhaka city markets (Islam et al., 2015; Jeddi et al., 2014; Kabir et al., 2014). In addition, when these pathogens were found resistant to multiple antibiotics, could pose significant public health risk and resistance of pathogenic bacteria could leads to the anti-infective therapy of both humans and animals (Lai et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Again, foodborne illness due to contaminated vegetables increased many folds worldwide and many research studies reported that the presence of pathogenic bacteria like E. coli O157:H7, Salmonella spp., Listeria spp., Staphylococcus spp., Yersinia enterocolitica etc. in various fresh vegetable samples of Dhaka city markets (Islam et al., 2015; Jeddi et al., 2014; Kabir et al., 2014). In addition, when these pathogens were found resistant to multiple antibiotics, could pose significant public health risk and resistance of pathogenic bacteria could leads to the anti-infective therapy of both humans and animals (Lai et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ready-to-eat (RTE) mixed vegetable salad which is now a major part of our daily meal in Nigeria and sold in fast food eateries is a mixture of fresh vegetables (carrot, cabbage, cucumber, green pepper, and lettuce), pre-packed baked beans and cream milk. The consumption of vegetable salad in Nigeria and other parts of the world has greatly increased based on the requirements of nutrients, vitamin A, iron, calcium, proteins, fats, minerals and the medical benefits of its constituents [1,2,3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Although the consumption of fresh and minimally processed vegetables is considered healthy, outbreaks related to the contamination of these products are frequently reported since they are not subjected to treatments that considerably reduce microbiological hazards [7]. Vegetables can be contaminated from different environmental sources, such as soil, water, insects, air, birds, animal or equipment during cultivation, harvesting, processing, transport and marketing [6,8,9]. A large number of pathogenic microorganisms including Listeria monocytogenes, Salmonella, Escherichia coli O157:H7, Bacillus anthracis, Mycobacterium spp., Brucella spp., Yersinia enterolytica, Clostridium perfringens, Klebsiella spp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations